Knowledge, attitude, and practice of dental patients toward dental defects and dental fillings in Jinan, Shandong Province, China: a mediation analysis - Hongyan Ye; Junru Meng; Jing Sun; Ru Li; Wei Wei; Shengnan Zhang; Hui Li; Wenyue Zhang; Yugang Sun (BMC, 2024)
Abstract Background Dental filling is a prevalent method for treating dental defects. This study aimed to investigate the knowledge, attitude, and practice (KAP) toward dental defects and dental fillings among dental patients in Jinan, Shandong Province, China. Methods This cross-sectional study was conducted at the main campus and several branch campuses of Jinan Stomatological Hospital, and community locations within Jinan city between October 2023, and January 2024. Spearman correlation analysis and mediation analysis were used to assess the associations and interrelationships between KAP scores. Results In this study, 2529 dental patients participated, with 69.1% being females. Of these, 1711 had no dental defects, 551 had defects and fillings, and 267 had defects without fillings. Their median knowledge, attitude, and practice (Questions 1-6) scores were 8.00 [5.00, 12.00] (possible range: 0-18), 27.00 [26.00, 29.00] (possible range: 10-50), and 19.00 [15.00, 24.00] (possible range: 9-45), respectively. Mediation analysis revealed that in patients without dental defects, knowledge had a direct effect on attitude (β = -0.983, 95% CI: -0.999, -0.966, P < 0.001). Additionally, attitude had a direct effect on practice (β = -0.797, 95% CI: -1.490, -0.103, P = 0.024), while knowledge had an indirect effect on practice through attitude (β = 0.783, 95% CI: 0.096, 1.470, P = 0.026). In patients with dental defects who had undergone dental fillings, significant direct effects were observed between knowledge and attitude (β = -0.736, 95% CI: -0.821, -0.650, P < 0.001), knowledge and practice (β = 0.396, 95% CI: 0.214, 0.577, P < 0.001), and attitude and practice (β = -0.499, 95% CI: -0.683, -0.315, P < 0.001). Moreover, knowledge had an indirect effect on practice (β = 0.367, 95 CI: 0.221, 0.513, P < 0.001). In patients with dental defects but without any fillings, direct effects were found between knowledge and attitude (β = -0.929, 95% CI: -1.028, -0.829, P < 0.001). Conclusions Dental patients had inadequate knowledge, attitude, and practices concerning dental defects and fillings. It is recommended that clinical interventions should focus on enhancing patient education and promoting positive engagement in dental care practices.